Composite cis-acting epigenetic switches in eukaryotes: lessons from Drosophila Fab-7 for the Igf2-H19 imprinted domain. - Brown, J.P.; Singh, P.B.; Cowell, I.G. (Genetica, 2003)
One of the central problems of eukaryotic gene regulation is to understand the mechanism(s) by which the activity of enhancer elements is circumscribed such that they only act upon their cognate promoter sequences. Studies on the bithorax gene complex (BX-C) in Drosophila have highlighted the potential problem of enhancer promiscuity and detailed molecular and genetic analyses are now providing insight into how this gene complex resolves the problem through the activity of boundary/silencer elements that can block the communication between enhancers and promoters. Analysis of the mouse Igf2-H19 imprinted locus also suggests a role for boundary/silencer elements, but in this case these elements are invoked to account for the preferential expression of Igf2 and H19 from the paternally and maternally inherited chromosomes respectively despite the presence of functional downstream enhancers. We discuss recent work that has illuminated both of these systems and consider what parallels exist between them.